UPAYA THE BODY SHOP DALAM MENDUKUNG PENERAPAN PRINSIP FAIR TRADE DI BIDANG LINGKUNGAN DALAM AKTIVITAS BISNISNYA - Mila Sari, Putu Wahyu; Sushanti, Sukma; Wiranata, I Made Anom (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRA CT Fair trade as an alternative trading system of free trade introducing moral values ??to a trading system that is useful for producers, consumers and the environment. Environment in the trading system is a resources, but also get a negative impact on trade. A multinational beauty company The Body Shop International is a company that supports fair trade in accordance with moral values of the company. By using the method of literature sourced from website s , journals, and ne ws , this study describes the shape of the support of The Body Shop, which is manifested especially in the field of environment ,  seen through its business activities , the company's internal and external (community fair trade The Body Shop . Through an external company, The Body Shop has been doing various activities such as Wood Positive, Wood Sourcing Policy, and several activities in the community fair trade (Kuapa Kokoo, Ghana and Candela, Peru) . I n the internal, The Body Shop implementing rules friendly to the environment.   Keywords : Fair Trade, environmental, The Body Shop, business activities (internal and external )